(untitled) (Orfeu, 2017)
The project “Creation Libretti: the experience of playing with sounds in Poetic Gatherings in Childhood Education” took place in the university’s studio with the objective of pursuing ways of recording the playful experience of language. The methodology of the Poetic Gatherings was sustained by a process of intense purposeful interaction, using the body as an instrument with excellent ability to move poetically to music, dance and literature, aiming at amplifying children’s and adults’ movement repertoire. While asserting the pedagogical relevance of group musical encounters, realized through the the complex process of learning to inventively express language, this study focuses reflectively on sound-play. This investigation contributes to broadening the themes addressed in musical education research, inviting regular investigation of educational curricula.